2012
DOI: 10.3945/ajcn.111.030114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n-6 PUFAs compared with SFAs on liver fat, lipoproteins, and inflammation in abdominal obesity: a randomized controlled trial

Abstract: Compared with SFA intake, n-6 PUFAs reduce liver fat and modestly improve metabolic status, without weight loss. A high n-6 PUFA intake does not cause any signs of inflammation or oxidative stress. Downregulation of PCSK9 could be a novel mechanism behind the cholesterol-lowering effects of PUFAs. This trial was registered at clinicaltrials.gov as NCT01038102.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
330
5
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 429 publications
(386 citation statements)
references
References 50 publications
27
330
5
6
Order By: Relevance
“…The effect of LA on ischemic stroke may act through several mechanisms. Numerous studies have thus reported a beneficial effect of LA on blood lipids and blood pressure 23, 24. Since hypercholesterolemia and hypertension have a different impact on the large precerebral arteries and the small cerebral arteries,9, 25, 26 this could partly explain the observed differences in risk between subtypes of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of LA on ischemic stroke may act through several mechanisms. Numerous studies have thus reported a beneficial effect of LA on blood lipids and blood pressure 23, 24. Since hypercholesterolemia and hypertension have a different impact on the large precerebral arteries and the small cerebral arteries,9, 25, 26 this could partly explain the observed differences in risk between subtypes of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…follow-up, this trial concluded that there was no significant 162 reduction in cardiovascular endpoints, although no serious IG3 adverse effects were noted (34]. While these data imply that IG4 omega-3 PUFA may be preferable to other forms, omega-6 PUFA JG5 may themselves be preferable to saturated fat, as a randomized 166 trial of supplementation in 61 obese people with omega-6 PUFA 167 versus saturated fat indicated lower hepatic steatosis, serum 168 insulin and inflammatory markers in the omega-6 group (35). 169 With respect to NAFLD in particular, a randomized, placebo 110 controlled trial in 60 pediatric patients with ultrasound 111 diagnosed NAFLD with supplementation of omega-3 PUFA (500 mg of docosahexaenoic acid) resulted in reduced liver fat and triglycerides and improved insulin sensitivity without weight gain [36].…”
Section: 2mentioning
confidence: 99%
“…The cholesterol-and triglyceride-lowering effects of ω-6 PUFA consumption in place of SFAs are of particular interest for dyslipidemic and IR subjects. However, data on the impact of this dietary substitution on lipoprotein metabolism in subjects with dyslipidemia associated with IR are limited and mixed (15)(16)(17)(18). Therefore, our ability to define optimal, evidence-based dietary guidelines for this population at high CVD risk remains limited.…”
Section: Introductionmentioning
confidence: 99%